2016
DOI: 10.1016/j.nanoen.2016.02.031
|View full text |Cite
|
Sign up to set email alerts
|

Planar versus mesoscopic perovskite microstructures: The influence of CH3NH3PbI3 morphology on charge transport and recombination dynamics

Abstract: Perovskite solar cells (PSCs) employing planar and mesoscopic architectures have both resulted in high efficiency devices. However, there is presently a limited understanding of the inherent advantages of both systems, particularly in terms of the charge transport and recombination dynamics. In the present study we characterize the relative benefits of the two most prominent CH 3 NH 3 PbI 3 morphologies, primarily through time-resolved microwave conductivity (TRMC) and time-resolved photoluminescence (TRPL) me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
70
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 78 publications
(79 citation statements)
references
References 61 publications
(36 reference statements)
5
70
1
Order By: Relevance
“…4a-d, respectively. Regions of contrasting intensity between neighboring grains and grain-clusters can be clearly seen in the PL maps, as identified previously [25,42]. Firstly, it is important to note the differing intensity scales for each image in Fig.…”
Section: Materials Characterizationsupporting
confidence: 62%
See 3 more Smart Citations
“…4a-d, respectively. Regions of contrasting intensity between neighboring grains and grain-clusters can be clearly seen in the PL maps, as identified previously [25,42]. Firstly, it is important to note the differing intensity scales for each image in Fig.…”
Section: Materials Characterizationsupporting
confidence: 62%
“…Yet, one of the most important connections between the perovskite microstructure and the optoelectronic performance is arguably related to the perovskite grain size and charge transport/recombination kinetics. Several studies have revealed clear correlations between the perovskite microstructure, charge-carrier mobilities and charge-carrier lifetimes, implying that large perovskite crystals with a low density of grain boundaries are advantageous [22][23][24][25]. These findings are in keeping with the relatively high mobilities and low trap-state densities observed in single-crystal organic-inorganic perovskites [26].…”
Section: Introductionmentioning
confidence: 62%
See 2 more Smart Citations
“…Comparison of the PL in Fig. 7b reveals that the samples with compact films made by sol aged for 4 h show the most obvious quenching effect, indicating that the exciton separation and transfer is most effective [37]. The biggest roughness of the TiO2 film from 4 h aged sol may provide the best contact between the TiO2 and perovskite film and offer the most effective electron transfer, and consequently reduce charge recombination at the interface between the perovskite and FTO or HTM.…”
Section: Resultsmentioning
confidence: 97%